Interest groups and efficient design of the Clean Development Mechanism under the Kyoto Protocol. (12th May 2004) - Michaelowa, Axel; Dutschke, Michael
The implementation of activities aimed at mitigating global greenhouse gas emissions is more cost-efficient in developing countries than in most of the industrialised world. Nevertheless, efficient mitigation may have adverse effects on equity. A Clean Development Mechanism (CDM) is therefore to assure that the interests of all parties implicated in Joint Implementation between industrialised and developing countries be equally represented. This mechanism was decided on at the Kyoto Conference of the Parties to the Framework Convention on Climate Change, but no provisions on the construction of the CDM were taken. We propose it to take the form of a clearinghouse and a project fund. In the light of game-theoretical analysis and practical experience collected during the pilot phase for Activities Implemented Jointly, which started in 1995, we advocate a clearly defined set of rules and incentives in order to balance the variety of interests involved and, at the same time, make the CDM an efficient instrument in mitigating climate change while preventing negative distributional implications.